The effect of bisphosphonate discontinuation on the incidence of postoperative medication-related osteonecrosis of the jaw after tooth extraction - Kang, Sang-Hoon; Park, Se-Jin; Kim, Moon-Key (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2020)
The discontinuation of bisphosphonate (BP) treatment before tooth extraction may induce medication-related osteonecrosis of the jaw (MRONJ). Whether the long-term discontinuation of BP treatment before tooth extraction affects the risk of developing MRONJ after tooth extraction or whether extended drug holidays induce systemic side effects remains unclear. The present study assessed the incidence of MRONJ among patients who underwent tooth extraction and did not discontinue BP therapy prior to the procedure. Patients were classified according to whether or not they discontinued BP therapy before tooth extraction. Differences in the incidence of MRONJ after tooth extraction were compared between the two groups using the chi-squared test. The BP-continuation (BPC) and BP-discontinuation (BPDC) groups included 179 and 286 patients, respectively. One patient in the BPC group and no patients in the BPDC group developed MRONJ ( =0.385). The patients in the BPDC group stopped receiving BP therapy at a mean of 39.0±35.5 months prior to tooth extraction. The possibility of pre-existing MRONJ in the extraction area must be considered during the extraction procedure. Routine discontinuation of BP medications for several months before the extraction procedure should be carefully considered, as evidence of its efficacy in reducing the development of post-extraction MRONJ is limited.